Balancing Pixels and Play: Assessing the Physical and Mental Health Impacts of Children's Video Gaming - Ramesh Kumar*
This article examines children's video gaming and its physical and mental health impacts. Over six decades, games have advanced to immersive 3D environments, with 90% of children gaming on various devices. Excessive gaming fosters sedentary lifestyles, obesity, musculoskeletal issues, and sleep and vision disruptions. Mentally, it can lead to addiction, social withdrawal, anxiety, depression, and isolation, as lonely children use gaming to cope. While some argue games promote relaxation, motivation, and learning through immersion, these benefits are negated when health suffers. The article concludes that parents must monitor and limit gaming to safeguard children's well-being, academic performance, and social development.